2019
DOI: 10.1002/mus.26435
|View full text |Cite
|
Sign up to set email alerts
|

Translation and validation of the arabic version of the myasthenia gravis activities of daily living scale

Abstract: Introduction We translated the myasthenia gravis (MG)‐specific activities of daily living (MG‐ADL) scale into Arabic (MG‐ADL‐A) and assessed its psychometric properties. Methods We assessed reliability using Cronbach's α, reproducibility using the intraclass correlation coefficient, and validity using Spearman's correlations with MG composite (MGC) score, MG‐specific manual muscle test (MG‐MMT), and MG quality‐of‐life revised Arabic version (MGQOL15R‐A). Differences in MG‐ADL‐A scores among patients with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Raggi et al (2017) also reported that MG-ADL and MGC results were well correlated. Alanazy et al (2019) found a similar result as well. These results were expected, as MGC and MG-ADL share common evaluation parameters.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Raggi et al (2017) also reported that MG-ADL and MGC results were well correlated. Alanazy et al (2019) found a similar result as well. These results were expected, as MGC and MG-ADL share common evaluation parameters.…”
Section: Resultssupporting
confidence: 72%
“…Test–retest reliability was excellent with an ICC of .96, indicating the reproducibility of MG-ADL-T. Test–retest results have also been found to be excellent in other languages (Alanazy et al, 2019; Lee et al, 2017; Raggi et al, 2017; Rozmilowska et al, 2018). The test–retest correlation of the MG-ADL-T was very high for all the items, similar to the original article, which reported a test–retest reliability of about 93.7% (Mukaka, 2012; Muppidi et al, 2011).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…However, given the fluctuating nature of MG and because the MG-specific outcome measures were derived from the last follow-up visit, one should acknowledge that the good outcomes reported here do not reflect long-term stability of the disease in our cohort. However, most of the patients in this study had previously participated in the study validating the Arabic versions of the MG-QOL15R and MG-ADL, 10,11 which involved collecting MG-specific outcome measure data at different times than data collected for this study. As these studies also report milder disease symptoms among the patients )MG-QOL15R-A: 84.6%; MG-ADL-A: 89.7%(, we can consider that the overall prognosis of patients in our cohort is good.…”
Section: Resultsmentioning
confidence: 99%